2018
DOI: 10.1111/pce.13320
|View full text |Cite
|
Sign up to set email alerts
|

INDEL variation in the regulatory region of the major flowering time gene LanFTc1 is associated with vernalization response and flowering time in narrow‐leafed lupin (Lupinus angustifolius L.)

Abstract: Narrow-leafed lupin (Lupinus angustifolius L.) cultivation was transformed by 2 dominant vernalization-insensitive, early flowering time loci known as Ku and Julius (Jul), which allowed expansion into shorter season environments. However, reliance on these loci has limited genetic and phenotypic diversity for environmental adaptation in cultivated lupin. We recently predicted that a 1,423-bp deletion in the cis-regulatory region of LanFTc1, a FLOWERING LOCUS T (FT) homologue, derepressed expression of LanFTc1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 84 publications
(114 reference statements)
3
75
0
Order By: Relevance
“…[45], and gene variation is probably to be the most direct cause for altering gene expression pattern. The expansion or contraction of SSR, the transition or transversion of SNP and the insertion or deletion of InDel in gene sequence or promoter region, all can lead to changes in gene expression pattern and function via mutation in CDS, UTR, intron or promoter region [46][47][48]. Gene sequence of AhSTP19 was found conservation in the two subspecies, but SNP and InDel in the promoter region caused altering of CREs.…”
Section: Discussionmentioning
confidence: 99%
“…[45], and gene variation is probably to be the most direct cause for altering gene expression pattern. The expansion or contraction of SSR, the transition or transversion of SNP and the insertion or deletion of InDel in gene sequence or promoter region, all can lead to changes in gene expression pattern and function via mutation in CDS, UTR, intron or promoter region [46][47][48]. Gene sequence of AhSTP19 was found conservation in the two subspecies, but SNP and InDel in the promoter region caused altering of CREs.…”
Section: Discussionmentioning
confidence: 99%
“…Thedeletions are associated with altered responsiveness to vernalization, flowering time, and expression of LanFTc1 in the absence of vernalization. A third smaller deletion, reported in Taylor et al, results in a unique intermediate phenotype which may be valuable for breeding purposes and expanding the agronomic adaptation of lupin to new and existing production regions. Additionally, the insertion/deletion (INDEL) variant series may also help to increase knowledge of how signalling within the vernalization pathway is mediated at a molecular level in legumes.…”
Section: Breeding For Improved Traits and Sustainable Yield In Legumesmentioning
confidence: 99%
“…In Europe and Australia, breeders independently found mutations which eliminated vernalization response in narrow‐leafed lupin, and these mutations predominate in breeding programmes in Europe and Australia to this day. Researchers in Australia have shown that these two mutations were caused by similar deletions in the promotor region of LanFTc1, a major flowering time gene in narrow‐leafed lupin (Taylor et al, ). Thedeletions are associated with altered responsiveness to vernalization, flowering time, and expression of LanFTc1 in the absence of vernalization.…”
Section: Breeding For Improved Traits and Sustainable Yield In Legumesmentioning
confidence: 99%
“…Several functional pathways have been identi ed that regulate the switch from vegetative to reproductive development. These include the photoperiodic, vernalization, ambient temperature, plant hormone, and autonomous owering pathways [1,[4][5][6][7][8][9][10]. Within these pathways, a number of genes have been identi ed as involved in owering time regulation, including CONSTANS-LIKE (COL) genes, phosphatidyl ethanolamine-binding protein (PEBP) genes and several members of MADS-Box gene family [1][2][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%